2021
DOI: 10.1111/1365-2656.13497
|View full text |Cite
|
Sign up to set email alerts
|

Sea temperature effects on depth use and habitat selection in a marine fish community

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…Temperature is a key environmental factor affecting fish activities [28]. It can directly and indirectly affect fish life activities, such as spawning [29], embryonic development [30,31], survival rate [32], feeding metabolism [33], migration [34], and habitat distribution [35]. Yellowfin tuna is a warm-water fish species that needs a certain water temperature to inhabit and spawn.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is a key environmental factor affecting fish activities [28]. It can directly and indirectly affect fish life activities, such as spawning [29], embryonic development [30,31], survival rate [32], feeding metabolism [33], migration [34], and habitat distribution [35]. Yellowfin tuna is a warm-water fish species that needs a certain water temperature to inhabit and spawn.…”
Section: Discussionmentioning
confidence: 99%
“…Fishes captured using hook-and-line can experience behavior selection against more active individuals (Alós et al, 2016), and MPA networks can help oppose this selection. Utilizing the same acoustic telemetry array in Tvedestrand fjord, Freitas et al (2021) showed that summer peaks in sea surface temperature represent challenges for cod residing in a fjord environment, while ballan wrasse (Labrus bergylta) and Atlantic pollack (Pollachius pollachius) retained their movement behavior. During such periods, cod were confined to deeper, cooler water masses-away from shallow habitats preferred during autumn and winter.…”
Section: Discussionmentioning
confidence: 99%
“…Surrounded by MPAs allowing hook-and-line-type fishing gear, the no-take zone enables studying effects of protection on fish (Figure 1 and Table 1). An acoustic telemetry array consisting of 56 acoustic receivers is deployed in the fjord, also including the no-take zone (for details, see Villegas-Ríos et al, 2017b;Thorbjørnsen et al, 2019;Freitas et al, 2021).…”
Section: Study Systemmentioning
confidence: 99%
“…In particular, transient visits to soft-bottom habitats by cod may have resulted in substantial shedding of eDNA particles and subsequent high detection rates of cod eDNA at both soft-and hard-bottom habitats. Similarly, vertical use of the water column by cod (Freitas et al, 2021), as opposed to limited movement within the vertical dimension by the remaining focal species, also likely contributed to the ubiquitous detection of cod eDNA across our surface water samples (Figure 3; Figure S5). As we only used 1 L samples and three qPCR replicates in this study, this possibly limited the ability for statistically discerning habitat patterns for cod.…”
Section: Codmentioning
confidence: 94%